Use of the Theoretical Domains Framework to evaluate factors driving successful implementation of the Accelerated Chest pain Risk Evaluation (ACRE) project. (December 2016) - Skoien, Wade; Page, Katie; Parsonage, William; Ashover, Sarah; Milburn, Tanya; Cullen, Louise
Abstract Background The translation of healthcare research into practice is typically challenging and limited in effectiveness. The Theoretical Domains Framework (TDF) identifies 12 domains of behaviour determinants which can be used to understand the principles of behavioural change, a key factor influencing implementation. The Accelerated Chest pain Risk Evaluation (ACRE) project has successfully translated research into practice, by implementing an intervention to improve the assessment of low to intermediate risk patients presenting to emergency departments (EDs) with chest pain. The aims of this paper are to describe use of the TDF to determine which factors successfully influenced implementation and to describe use of the TDF as a tool to evaluate implementation efforts and which domains are most relevant to successful implementation. Methods A 30-item questionnaire targeting clinicians was developed using the TDF as a guide. Questions encompassed ten of the domains of the TDF:Knowledge ;Skills ;Social/professional role and identity ;Beliefs about capabilities ;Optimism ;Beliefs about consequences ;Intentions ;Memory, attention and decision processes ;Environmental context and resources ; andSocial influences . Results Sixty-three of 176 stakeholders (36 %) responded to the questionnaire. Responses for all scales showed that respondents were highly favourable to all aspects of the implementation. Scales with the highest mean responses were Intentions, Knowledge, and Optimism, suggesting that initial education and awareness strategies around the ACRE project were effective. Scales with the lowest mean responses were Environmental context and resources, and Social influences, perhaps highlighting that implementation planning could have benefitted from further consideration of the factors underlying these scales. Conclusions The ACRE project was successful, and therefore, a perfect case study for understanding factors which drive implementation success. The overwhelmingly positive response suggests that it was a successful programme and likely that each of these domains was important for the implementation. However, a lack of variance in the responses hampered us from concluding which factors were most influential in driving the success of the implementation. The TDF offers a useful framework to conceptualise and evaluate factors impacting on implementation success. However, its broad scope makes it necessary to tailor the framework to allow evaluation of specific projects.